UHRF1 binds G9a and participates in p21 transcriptional regulation in mammalian cells - Kim, Jong Kyong (Oxford University Press, 2009)
UHRF1 (ubiquitin-like, containing PHD and RING finger domains 1) is a multi-domain protein associated with cellular proliferation and epigenetic regulation. The UHRF1 binds to methylated CpG dinucleotides and recruits transcriptional repressors DNA methyltransferase 1 (DNMT1) and histone deacetylase 1 (HDAC1) through its distinct domains. However, the molecular basis of UHRF1-mediated transcriptional regulation via chromatin modifications is yet to be fully understood. Here we show that UHRF1 binds histone lysine methyltransferase G9a, and both are co-localized in the nucleus in a cell-cycle-dependent manner. Concurrent with the cell-cycle progression, gradual deposition of UHRF1 and G9a was observed, which mirrored H3K9me2 accumulation on chromatin. Murine Uhrf1-null embryonic stem (ES) cells displayed a reduced amount of G9a and H3K9me2 on chromatin. UHRF1 recruited and cooperated with G9a to inhibit the p21 promoter activity, which correlated with the elevated p21 protein level in both human UHRF1 siRNA-transfected HeLa cells and murine Uhrf1-null ES cells. Furthermore, endogenous p21 promoter remained bound to UHRF1, G9a, DNMT1 and HDAC1, and knockdown of UHRF1 impaired the association of all three chromatin modifiers with the promoter. Thus, our results suggest that UHRF1 may serve as a focal point of transcriptional regulation mediated by G9a and other chromatin modification enzymes.